Bilateral adrenal masses secondary to fungal infiltration in an immuno-competent host - Shahar, Mohammad Arif; Omar, Ahmad Marzuki; Rajoo, Subashini; Loh , Huai Heng; Ooi, Chew Peng; Wan Seman, Wan Juani; Omar, Mohd Rahman; A Wahab, Norasyikin; Mustafa, Norlaila; Sukor , Norlela; Kamaruddin, Nor Azmi (Malaysian Endocrine and Metabolic Society, 2014)
We presented a 54 year old gentleman, non-diabetic or hypertensive, presented with chronic headache worse in the afternoon, associated with late afternoon lethargy, loss of weight and loss of appetitefor 2 months duration. At presentation he was hypotensive, hyponatremic with relative hyperkalemia and low normal blood sugar. Six a.m. cortisol was 160 mmol/L. His hypotension and hyponatremia resolved after administration of intravenous hydrocortisone 100mg tid. Computed tomography (CT) of the adrenalsrevealedbilateral adrenal masses measuring 6.2 cm (largest diameter) on the left side and 5.0 cm on the right side (figure 1). CT guided biopsy of the adrenal mass revealed the presence of necrotic tissue with fungal bodies (figure 2 and figure 3). Retroviral screen was negative. On further questioning, the patient had been nursing an owl and had been handling its droppings 2 months prior to the onset of symptoms. This case illustrates the rare occurrence of bilateral adrenal mass from fungal infiltrationcausing adrenal insufficiency in an immuno-competent host with possible zoonosis from an owl.